Anatomical variations in the maxillary anterior region: a cone beam computed tomographic study of the canalis sinuosus and its accessory canals - Veronezzi, Matheus Chaves; Pinheiro, Igor Henrique Silva; Tolentino, Elen de Souza; Camarini, Camila; Takeshita, Wilton Mitsunari [UNESP]; Iwaki, Lilian Cristina Vessoni; Silva, Mariliani Chicarelli da (My University, 2023)
The objective of this study was to verify the frequency, diameter, and location of the canalis sinuosus (CS) and its accessory canals (ACs) using cone beam computed tomographic (CBCT) images and to correlate these findings with patient sex, age, and skeletal facial pattern. This observational retrospective study assessed the CBCT scans of 398 patients. The laterality, diameter, and location of the terminal portion of the canals were recorded. Linear measurements of the nasal cavity floor, buccal cortical bone, and alveolar ridge crest were also made. The χ2 and Fisher exact tests were used to verify the relationships between patient sex, age, and facial pattern and the presence of CS and ACs. The presence of CS and ACs was verified in 195 (48.99%) and 186 (46.73%) individuals, respectively, and showed no correlations with sex, age, or facial pattern. In 165 cases (84.61%), the CS emerged bilaterally. For ACs, most cases (n = 97; 52.14%) were unilateral. A total of 277 ACs were detected, and 161 (58.12%) of these were located in the palatal or incisive foramen region and 116 (41.88%) in the buccal region. Their terminal portions were located more frequently in the central incisor region (38.26%). The mean CS diameter was significantly larger
Keywords: alveolar process; anatomical variation; canalis sinuosus; cone beam computed tomography